Risk of Short-Term Mortality after Intracerebral Haemorrhage due to Weekend Hospital Admission in Poland. (9th December 2020) - Nowakowska-Kotas, Marta; Waliszewska-Prosół, Marta; Papier, Paulina; Budrewicz, Sławomir; Bańkowski, Tomasz; Pokryszko-Dragan, Anna
Abstract : Background . The mortality rate for spontaneous intracerebral haemorrhage (ICH) has remained high and stable for many years. The unfavourable prognostic factors include age, bleeding volume, location of the haematoma, high blood pressure, and disturbed consciousness on admission. Other risk factors associated with medical care also deserve attention. The study aimed to analyse the relationship between day of admission, concerning other prognostic factors, and short-term mortality in ICH, in a Polish specialist stroke unit. Methods . Medical records of 156 patients (74 males, 82 females, mean age 68.7 years) diagnosed with spontaneous ICH and admitted to a specialist stroke center were retrospectively analysed. Demographics, location, volume of bleeding, blood pressure values, and the Glasgow Coma Scale (GCS), as well as the day of admission, were determined. The relationships were analysed between these factors and 30-day mortality in the patients with ICH. Results . A total of 83 patients were admitted to the hospital during weekdays (Monday 8 am to Friday 3 pm) and 73 during weekends or holidays. Of these, 65 patients died within 30 days. Patients admitted at weekends initially presented with lower GCS scores. Admission on Saturday was associated with an increased risk of death (OR 3.38, 95% CI 1.2–9.48, p < 0.05 ), but after correction for clinical state measured with the GCS and ICH score, the association was no longer significant. Conclusions . The time and mode of admission were not associated with increased risk of short-term mortality in ICH patients. Prehospital care issues should be additionally considered as prognostic factors of the outcome.